Aplastic anemia during pregnancy: a review of obstetric and anesthetic considerations - Riveros-Perez E; Hermesch AC; Barbour LA; Hawkins JL (International Journal of Women's Health, 2018)
Efrain Riveros-Perez,1 Amy C Hermesch,2 Linda A Barbour,3 Joy L Hawkins4 1Department of Anesthesiology and Perioperative Medicine, Medical College of Georgia, Augusta University, Augusta, GA, 2Maternal Fetal Medicine, 3Obstetrics and Gynecology, 4Department of Anesthesiology, University of Colorado School of Medicine, Aurora, CO, USA Abstract: Aplastic anemia is a hematologic condition occasionally presenting during pregnancy. This pathological process is associated with significant maternal and neonatal morbidity and mortality. Obstetric and anesthetic management is challenging, and treatment requires a coordinated effort by an interdisciplinary team, in order to provide safe care to these patients. In this review, we describe the current state of the literature as it applies to the complexity of aplastic anemia in pregnancy, focusing on pathophysiologic aspects of the disease in pregnancy, as well as relevant obstetric and anesthetic considerations necessary to treat this challenging problem. A multidisciplinary-team approach to the management of aplastic anemia in pregnancy is necessary to coordinate prenatal care, optimize maternofetal outcomes, and plan peripartum interventions. Conservative transfusion management is critical to prevent alloimmunization. Although a safe threshold-platelet count for neuraxial anesthesia has not been established, selection of anesthetic technique must be evaluated on a case-to-case basis. Keywords: aplastic anemia, platelets, high-risk obstetrics, obstetric anesthesia, pregnancy